FAKTOR YANG BERHUBUNGAN DENGAN KEAKTIFAN KADER POSYANDU DI WILAYAH KERJA PUSKESMAS RANOTANA WERU - Nonce N. Legi; Fred Rumagit; Ana B. Montol; Riaty Lule (Jurnal GIZIDO, 2015)
Posyandu is one form of Community Based Health Efforts are managed and held on by, for andwith the community in the organization of health development, in order to deceive the public inobtaining basic health services to accelerate the reduction in maternal and infant kemaratiannumbers. The sustainability of this activity is highly dependent on the active participation of healthcadres as the main implementers. The purpose of this research is to know about the factorsassociated with the activity cadre's in Puskesmas Ranotana WeruKota Manado.Type of survey research with deskristif approach. This implementation is implemented in May 2015in Manado City Health Center Ranotana Weru. Population is all cadres Posyandu in PuskesmasRanotana Weru Manado City. Samples are 45 cadres, with the data obtained using a questionnaire(liveliness cadres, cadres of knowledge, training of cadres, cadres keposyandu distance home,support the husband / family). While secondary data obtained from health centers. Tools andbahanyang used questionnaires, Calculator, leptop, SPSS Program.The results showed 39 0rang (86.7%) belongs to the category health cadres active in theimplementation of integrated health activities, 42 (93.3%) high school educated cadres, cadresknowledgeable 95.6% good, 88.9% of cadres who had attended Posyandu cadre training, 0rang 29(64.4%) which has a distance cadre's home near denganposyandu, and 44 (97.8%) cadre's whohas the support of husband / family.